Bioremediation of soils contaminated by hydrocarbons using animal manure, a systematic review during the years 2017-2022. (LACCEI, 2024)
Currently, due to the high worldwide demand for hydrocarbons demand for the use of hydrocarbons is causing serious impacts on soil fertility, properties and use, as well as fertility, properties and use of the soil, as well as on people, flora and fauna. people, flora and fauna. This systematic review aims to the bioremediation of hydrocarbon-contaminated soils using manure contaminated by hydrocarbons using animal manure through the use of PRIS the use of PRISMA methodology in order to gather information that describes the information describing the effectiveness of animal manure in the bioremediation of contaminated soils.bioremediation of hydrocarbon contaminated soils. According toAccording to the results, cow and poultry manure are the most commonly and poultry manure are the most used, presenting 21-99% and 80-96% respectively of hydrocarbon percentage of hydrocarbon degradation in soils. In addition, the African continent had the highest percentage of hydrocarbon degradation in soils, The African continent was the one with the largest number of studies, due to the fact that it is a rich the African continent was the one with the greatest number of studies, due to the fact that it is an area rich in oil. It is concluded that the use of animal manure of animal manure is an effective, efficient and reliable technique for the removal of hydrocarbons in different soils. removal of hydrocarbons in different types of soils, and its degradation percentage of degradation would be improved by adding bacterial or plant species.